The state of creativity in adolescents with intellectual disabilities - Yeremenko, H.Yu.; Yakovleva, S.D.; Sagan, O.V. (Amazonia Investiga, 2021)
The objective of the article is to investigate empirically and substantiate theoretically the state of creativity in adolescents with intellectual disabilities; to reveal gender differences and changes in creativity during puberty in 13-15-year old adolescents. Davis's standardized technique was used to determine the respondents’ creativity. Obtained data were processed using Student’s t-test for paired samples. The obtained results showed existing but not realized capabilities of adolescents with intellectual disabilities, so special correctional and developmental work should be performed with them.